1997
DOI: 10.1212/wnl.49.6.1525
|View full text |Cite
|
Sign up to set email alerts
|

Normalization of neuronal metabolic dysfunction after surgery for temporal lobe epilepsy

Abstract: Surgery is a safe and effective treatment for patients with temporal lobe epilepsy (TLE) who do not respond adequately to anticonvulsant medication and in whom the seizure generator can be identified and safely removed. Proton MR spectroscopic imaging (MRSI) can image and quantify neuronal damage in patients with TLE based on reduced signals from N-acetylaspartate (NAA), a compound localized exclusively in neurons. We performed proton MRSI in patients with TLE before and after surgical treatment to determine w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
142
0
12

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(167 citation statements)
references
References 10 publications
13
142
0
12
Order By: Relevance
“…However Hugg's report of NAA recovery from the contralateral hippocampus in patients with bilateral abnormalities one year after successful surgery (41) suggested that at least a portion of the observed NAA loss was not solely due to neuronal loss. This finding was later confirmed by Cendes (42). In a follow-up study 50%, on average, of the metabolic recovery occurred over a period of less than six months, demonstrating a slow but responsive nature of neuronal NAA levels (43).…”
Section: Biological Interpretation Of Metabolic Changesmentioning
confidence: 66%
“…However Hugg's report of NAA recovery from the contralateral hippocampus in patients with bilateral abnormalities one year after successful surgery (41) suggested that at least a portion of the observed NAA loss was not solely due to neuronal loss. This finding was later confirmed by Cendes (42). In a follow-up study 50%, on average, of the metabolic recovery occurred over a period of less than six months, demonstrating a slow but responsive nature of neuronal NAA levels (43).…”
Section: Biological Interpretation Of Metabolic Changesmentioning
confidence: 66%
“…While the biological role of NAA has yet to be clearly defined, it acts via the glutamatergic NMDA receptor to elevate intracellular calcium (Rubin et al 1995), and its concentrations are reduced by pharmacological inhibition of mitochondrial energy metabolism (Bates et al 1996) as well as by a number of pathological processes affecting the integrity of neurons (Cendes et al 1997;De Stefano et al 1995;Najim et al 1998). Other data also suggest that NAA concentrations vary with the structural and functional state of glutamatergic cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NAA increases during pharmacologically induced status epilepticus and then decreases after neuronal damage has occurred (Najim et al 1998). Surgical removal of the epileptic focus in temporal lobe epilepsy reverses NAA decreases not only in the affected side but also in the contralateral side, presumably by modulating abnormal interhemispheric glutamatergic projections (Cendes et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The recovery of NAA in the ipsilateral and contralateral temporal lobes after successful surgical treatment of the epilepsy [28,29] indicates that widespread decreases in NAA in patients with TLE primarily reflect neuronal dysfunction rather than irreversible neuronal loss.…”
Section: Discussionmentioning
confidence: 99%